Nasopharyngeal masses in adults—A retrospective analysis of 255 patients to evaluate symptoms, clinical findings, and histological results - Melanie M. vonWitzleben; Adrian vonWitzleben; Thomas K. Hoffmann; Janina Hahn (World Journal of Otorhinolaryngology-Head and Neck Surgery)
Abstract Background Nasopharyngeal tissue hyperplasia is generally associated with adenoids in childhood. In adults, nasopharyngeal masses are occasionally found, but data on symptoms, clinical findings, and histologic results are limited. Material and Methods A 10‐year retrospective study was conducted, analyzing data from adult patients who underwent nasopharyngeal biopsies. The study included information on case history, preoperative suspected diagnosis, and histology type. Statistical analysis was performed. Results Two hundred and fifty‐five patients were included, most of them complaining of nasal obstruction, ear pressure, and hearing loss. Biopsy revealed adenoid tissue (64.7%), solid malignancies (15.7%; dominant undifferentiated carcinoma), lymphomas (9.0%), cysts (7.8%), and other benign tumors (2.7%). Malignant neoplasms were predominantly found in male and in elderly patients (P < 0.0001). If a malignant tumor was suspected initially, histological examination confirmed this in 75% of the cases. 45% of patients with a malignant nasopharyngeal mass had a unilateral seromucous tympanum. Conclusions Persistent nasopharyngeal masses in adults—particularly in elderly men, smokers and those with simultaneous unilateral seromucous tympanum—should undergo a histological examination.